The Bourne ultimatum [videorecording (DVD)] - Greengrass, Paul; Damon, Matt; Stiles, Julia, 1981-; Strathairn, David; Ludlum, Robert, 1927-2001 (Universal Studios Home Entertainment, 2007)
Bourne is once again brought out of hiding. This time, inadvertently by London-based reporter Simon Ross. Simon is trying to unveil Operation BlackBriar which is an upgrade to Project Treadstone, by writing about it in a series of newspaper columns. Bourne sets up a meeting with Ross and realizes instantly they're being scanned. Information from the reporter stirs a new set of memories, and Bourne must finally, ultimately, uncover his dark past whilst dodging The Company's best efforts in trying to eradicate him.